A review of the black clam (Villorita cyprinoides) fishery of the Vembanad Lake - Laxmilatha, P; Appukuttan, K K (Indian Journal of Fisheries, 2011)
The black clam, Villorita cyprinoides, is an important fishery of the VembanadLake and contributes to over 70% of the total fish production from the Lake.Factors which affect the sustainability of this fishery are indiscriminate exploitationof small-sized clams, closure of the Thaneermukham Barrage, frequentdredging, pollution due to retting, effluents from shrimp processing plants /factories and swarming of weeds. The present status and management optionsfor this important fishery are discussed.